Relevance of a physical activity rehabilitation care pathway based on the experience and commitment of people suffering of obesity - Bourgeois, Elise; Lognos, Béatrice; Sultan, Ariane (BMC public health, 2025)
Context Despite the benefits of physical activity, people suffering from obesity face a number of obstacles and often give up. The proposed care pathway integrates multidisciplinary management of people suffering from obesity. It aims to assess the impact of adapted physical activity: a supervised practice tailored to each individual’s state of health, abilities and needs. It was offered to eighty people during their day hospitalization at Montpellier University Hospital; forty-six started and eight stopped during the three-month course. Eligibility criteria included a body mass index (BMI) greater than 30 kg/m² and the presence of musculoskeletal pain requiring physiotherapy. Our main aim was to identify the factors structuring patients’ involvement, by collecting their experiences and views. Method The study is based on a qualitative content analysis of data collected during semi-structured interviews with all participants. The comments were segmented into units of meaning, then organized into a matrix of conceptual groupings. This process enabled the emergence of cross-cutting themes. The inductive approach we adopted led us, initially, to stay as close as possible to what we heard, avoiding any premature interpretation. Inscribed in a constructivist posture, this initial phase formed the basis for a more in-depth analysis. Results Analysis of the thirty-five interviews carried out revealed the following determinants: The interpersonal relationship between the professional and the patient, which must lead the former to value the latter and build mutual trust; - The question of patient autonomy, through the difficulty they express in taking charge of their own care, or in the need they express to benefit from additional follow-up at the end of the care pathway; - The need for flexibility on the part of patients, who conversely wish to become actors in their own care pathway; - Coordination and communication, notably with the necessary sharing of patient information, and the integration of relatives into the care pathway. These results lead to the formulation of several proposals with practical implications for the deployment of a care pathway. Conclusion These relational, organizational and personal determinants structure patient involvement, and need to be taken into account right from the design phase. The success of a healthcare program depends on the stakeholders’ ability to identify them and ensure that the objectives set are achievable. A care pathway that takes these factors into account increases the likelihood of successful patient outcomes.